Initial development of three blue lupin (Lupinus angustifolius L.) varieties in northern Finland - Aniszewski, Tadeusz (Agricultural Research Centre, 1988)
Sarja Peltoviljely n:o 89 V ok Kolmen sinilupiinilajikkeen (Lupinus angustifolius L.) alkukehitys Suomessa